Building Sustainability Resiliency During Post Covid World Focusing ESG And Climate Risk Issue - Afreen, Maria (Innovation Journal of Social Sciences and Economic Review, 2021)
This study evaluates the impact of climate-related risks on global financial stability, emphasizing both physical and transitional risks. It explores the influence of these risks on ESG (Environmental, Social, and Corporate Governance) goals, particularly within the context of the European Green Deal and post-COVID-19 recovery efforts. Utilizing a dynamic common factor model, the research analyzes time-series data from 2010 to 2019 to measure relative and absolute carbon risks across regions such as Europe, North America, Japan, and the Eurozone. The Kalman filter tool facilitates a detailed examination of regional carbon emissions and associated risks. Findings reveal that relative carbon risk is highest in North America, followed by Japan, Europe, and the Eurozone. In contrast, absolute carbon risk is most pronounced in the Eurozone, with Europe and North America trailing. The study highlights that absolute carbon risk surpasses relative carbon risk globally, underscoring the need for more aggressive and region-specific risk mitigation strategies. The study concludes that current climate risk management strategies require enhancement to effectively address rising carbon risks. Financial institutions play a critical role in supporting global sustainability goals, especially in the post-pandemic era. The implications suggest that policymakers and financial institutions must intensify their focus on climate risk management, particularly in high-risk regions. Strengthening data collection and analytical capabilities is essential for improving the accuracy of climate risk assessments, supporting global cooperation in achieving ESG goals, and ensuring financial stability amidst escalating climate risks.